2009
DOI: 10.1107/s0021889809048006
|View full text |Cite
|
Sign up to set email alerts
|

X-ray diffraction study of a pseudo single crystal prepared from a crystal belonging to point group 2

Abstract: A pseudo single crystal (a composite of matrix resin and powder crystallites, wherein the individual crystallites are aligned three‐dimensionally) was prepared from a powder of sucrose, and its X‐ray diffraction pattern was studied. A powder of sucrose crystals suspended in a UV‐curable resin precursor was subjected to magnetic alignment in order to align the individual crystallites three‐dimensionally, and then the resin precursor was photopolymerized to maintain this orientation. The pseudo single crystal th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 7 publications
0
28
0
Order By: Relevance
“…The MOMA method is applicable to the biaxial crystal systems including the triclinic, monoclinic, and orthorhombic systems. We have reported the X-ray measurements of MOMAs fabricated from L-alanine [15], LiCoPO 4 [16], sucrose [17], and lysozyme [19] microcrystalline powders, which gave rise to diffraction patterns similar to those of the corresponding single crystals. The crystal structures determined from the MOMAs were in good agreement with those reported for the corresponding single crystals in the literature.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The MOMA method is applicable to the biaxial crystal systems including the triclinic, monoclinic, and orthorhombic systems. We have reported the X-ray measurements of MOMAs fabricated from L-alanine [15], LiCoPO 4 [16], sucrose [17], and lysozyme [19] microcrystalline powders, which gave rise to diffraction patterns similar to those of the corresponding single crystals. The crystal structures determined from the MOMAs were in good agreement with those reported for the corresponding single crystals in the literature.…”
Section: Introductionmentioning
confidence: 91%
“…A MOMA is a composite in which microcrystals are aligned three-dimensionally [14][15][16][17][18][19]. The concept of the three-dimensional crystal alignment was reported in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, a large single crystal is required to obtain sufficient S/N from the samples; this requirement limits the use of single crystals in NMR because it is difficult to grow large crystals under many circumstances. Previously, we have shown that microcrystals suspended in a liquid medium can undergo biaxial alignment when subjected to frequency-modulated rotating magnetic fields [12][13][14][15][16]. By solidifying the liquid medium after the alignment, we obtain a magnetically oriented microcrystal array (MOMA), which is a polymer composite with embedded microcrystals that are three-dimensionally aligned.…”
Section: Introductionmentioning
confidence: 99%
“…The crystallographic and magnetic axes are shown schematically in Fig. 2b, where the b axis and axis are placed perpendicular to the plane of the diagram (F. Kimura et al, 2010b). Since the three magnetic susceptibility axes are mutually perpendicular, the other two magnetic susceptibility axes are placed on the plane of the diagram.…”
Section: Theoretical Background Of Preparation Of a 3d-momamentioning
confidence: 99%